2006
DOI: 10.1111/j.1740-0929.2006.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fermented persimmon shell diet supplementation on the growth performance and blood parameters in finishing pigs

Abstract: The objective of the present study was to investigate the effects of fermented persimmon shell diet (FPSD) supplementation on growth performance and blood parameters in 96 Berkshire pigs. The FPSD was made from persimmon shell and mixed with rice bran and barley bran. Samples of FPSD on day 0 (D0) and day 60 (D60) were analyzed for chemical composition, pH and organic acids. The experimental diets were 0, 3, 5 and 7% FPSD added to C, T1, T2 and T3 of finishing diets on fresh matter basis. Dry matter (DM) was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Kim et al . () and Lee et al . () reported that feeding finishing pigs fermented persimmon shell or fermented off‐grade apple improved feed efficiency compared with a control group fed with ordinary feed.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Kim et al . () and Lee et al . () reported that feeding finishing pigs fermented persimmon shell or fermented off‐grade apple improved feed efficiency compared with a control group fed with ordinary feed.…”
Section: Resultsmentioning
confidence: 87%
“…The decreasing WHC in the APMS treatment groups agrees with the findings of Kim et al . (), who reported that a diet of over 5% fermented persimmon shells decreased the WHC of pork.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Song et al (2007) reported that supplementation of diet with 7% fermented mushroom by-products decreased the ADG and feed efficiency in pigs. Kim et al (2006) also reported that supplemental fermented persimmon shell diet influenced the growth performance via increased organic acids in finishing pigs. The ADG and feed efficiency were associated with reduced nutrient values of FMBD such as a low concentration of EE and high concentration of CF in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The microorganism-fermented diet improved gastrointestinal environment, such as decreased gastric pH, number of enteric pathogens and incidences of clinical diseases, and increased concentration of gastric lactic acid Lee et al, 2009). It was also reported that microorganism-fermented diet improved palatability and animal health (Canibe and Jensen, 2007;Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%